PEMAKNAAN SANDWICH GENERATION dALAM QS AL-BAQARAH AYAT 215 : (Studi Analisis Tafsir Al-Fakhr Ar-Razi) - Kahfi Maulana Nursadin; Banna Naelin Najihah (Al Kareem Jurnal Ilmu Al Qur'an dan Tafsir, 2025)
This study explores how the "Sandwich Generation" interprets Qur’anic verse Al-Baqarah 215 through the lens of Ar-Razi’s classical tafsir. The Sandwich Generation refers to individuals who bear simultaneous financial and emotional responsibilities for both their aging parents and their children. Employing a qualitative approach based on literature review, the research applies Gary Becker's theory of family economics and social welfare to analyze how these individuals prioritize their obligations. The findings suggest that the interpretation of Al-Baqarah 215 provides religious justification and ethical guidance for managing multigenerational responsibilities. This analysis contributes to understanding how Islamic teachings are utilized by modern Muslim families to navigate complex familial roles.